Miguel Díaz Cueva: varón de justicia y caridad - Cevallos García, Gabriel. 1913-2004
Contiene:Biografías de Alfonso maria mora, Remigio Tamariz Crespo. Ricardo MArquez Tapia. Luis moreno Mora. Alfonso Cordero Palacios. Manuel Ignacio Ochoa Alvear. Miguel Angel Moreno Serrano. Roberto Crespo Ordoñez. Ines de Jesús Cordero Dávila, Nicanos Merchán Bermeo